Genetic diversity and population structure in Ethiopian Urochloa brizantha genotypes uncovered using inter simple sequence repeat (ISSR) markers - Meheret, F.; Tesfaye, K.; Haileselassie, T.; Muktar, Meki (Public Library of Science, 2026)
Urochloa brizantha is a tropical C4 grass belonging to the Urochloa genus. Despite its immense potential as animal feed and its contribution to livestock production in sub-Saharan African countries, particularly Ethiopia, its utilization remains limited due to an inadequate supply of Urochloa cultivars and an insufficient genetic characterization of currently available genotypes. Hence, this study was conducted to assess the genetic diversity and population structure of 66 U. brizantha genotypes from the Ethiopian collection by leveraging six polymorphic inter-simple sequence repeat (ISSR) markers. These markers generated a total of 80 scoring bands, with 79 of which were polymorphic, and an average of 13.33 bands per primer. The polymorphism information content (PIC) ranged from 0.31 to 0.34, revealing the significance of these ISSR markers in uncovering highly polymorphic loci across the genotypes. Analysis of Molecular Variance (AMOVA) revealed that 69.68% of the genetic variability was distributed within the population, while the remaining variation was among populations. Genotypes collected from Illubabor revealed the highest degree of genetic diversity (PPL = 81.25% and Shannon’s information index = 0.34 ± 0.24), while the genotypes from central Gondar exhibited the least genetic diversity (PPL = 51.25% and Shannon’s index = 0.28 ± 0.27). The 66 genotypes of U. brizantha were grouped into seven clusters (K = 7) based on STRUCTURE analysis and the unweighted pair group method with arithmetic mean (UPGMA) algorithm after the formation of three major clusters at the root. These genotype collections generally formed their own cluster following their regional collection, though cluster analysis also revealed genetic admixture. These results illustrated the extent of genetic diversity within Ethiopian U. brizantha genotypes, confirming their potential for conservation and forage improvement. This could provide an alternative source of animal feed in sub-Saharan Africa, where feed shortages are a significant constraint to sustainable livestock production.